The construction of a juridical ontology - Alves, Isa Mara da Rosa [UNESP]; Chishman, Rove Luiza de Oliveira; Torres, Paulo Miguel; Quaresma, Duarte (Association for Computing Machinery (ACM), 2007)
The need for the representation of both semantics and common sense and its organization in a lexical database or knowledge base has motivated the development of large projects, such as Wordnets, CYC and Mikrokosmos. Besides the generic bases, another approach is the construction of ontologies for specific domains. Among the advantages of such approach there is the possibility of a greater and more detailed coverage of a specific domain and its terminology. Domain ontologies are important resources in several tasks related to the language processing, especially in those related to information retrieval and extraction in textual bases. Information retrieval or even question and answer systems can benefit from the domain knowledge represented in an ontology. Besides embracing the terminology of the field, the ontology makes the relationships among the terms explicit. Copyright 2007 ACM.
Keywords: Database systems; Information retrieval; Information retrieval systems; Knowledge based systems; Knowledge representation; Semantics; Juridical ontology; Lexical database; Textual bases; Ontology